The equation of circle is
![x ^{2} + y ^{2} - 16 = 0](https://tex.z-dn.net/?f=x%20%5E%7B2%7D%20%20%2B%20y%20%5E%7B2%7D%20-%2016%20%3D%200)
(X)+2(x+1)=26
3x=24
X=8
Y=x+1
Y=8+1
Y=9
The two numbers are 8 and 9
Answer:
Angle E is 30⁰
Explanation:
If triangle ABC= triangle DFE then they are both the same it's just that in this case the triangles are mirrored meaning that Angle C= Angle E
Making Angle E: 30⁰
Answer:
2x+59.
Step-by-step explanation:
Let <em>J </em>represent Jessica's weight and <em>R</em> represent Ronda's weight.
Jessica weighs <em>x+34</em> pounds. Thus:
![J=x+34](https://tex.z-dn.net/?f=J%3Dx%2B34)
Ronda weighs 12 pounds less than Jessica. In other words:
![R=J-12=(x+34)-12\\R=x+22](https://tex.z-dn.net/?f=R%3DJ-12%3D%28x%2B34%29-12%5C%5CR%3Dx%2B22)
The sum of their weights, therefore, is:
![J+R\\=(x+34)+(x+22)=2x+56](https://tex.z-dn.net/?f=J%2BR%5C%5C%3D%28x%2B34%29%2B%28x%2B22%29%3D2x%2B56)
Now, if Jessica gains 5 pounds and Ronda loses 2 pounds, the net gain of the total weight would be 3 pounds. Thus, we only need to add 3 to the original total to find the sum of their new weights:
![2x+56+3=2x+59](https://tex.z-dn.net/?f=2x%2B56%2B3%3D2x%2B59)
The sum of the new [weights] is represented by 2x+59.
Answer:
Step-by-step explanation:
(x + 2)(x +9)= x*(x +9) + 2*(x +9)
= x*x + x*9 + 2*x + 2*9
= x² +<u> 9x + 2x </u>+ 18 {Combine like terms}
= x² + 11x +18